Die gebeukte kind - Margaretha C. van Huyssteen (AOSIS, 1980)
The nurse, and especially the midwife and community health nurse, can make a major contribution towards the prevention of child abuse by developing a sensitivity in respect of the contributing factors which make of a parent a potential abuser of children, by helping to identify these parents, by giving the necessary assistance and guidance and by providing sources of reference where necessary.